2015
DOI: 10.1073/pnas.1413090112
|View full text |Cite
|
Sign up to set email alerts
|

Joint control of terrestrial gross primary productivity by plant phenology and physiology

Abstract: Terrestrial gross primary productivity (GPP) varies greatly over time and space. A better understanding of this variability is necessary for more accurate predictions of the future climate-carbon cycle feedback. Recent studies have suggested that variability in GPP is driven by a broad range of biotic and abiotic factors operating mainly through changes in vegetation phenology and physiological processes. However, it is still unclear how plant phenology and physiology can be integrated to explain the spatiotem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
244
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 308 publications
(259 citation statements)
references
References 53 publications
11
244
1
3
Order By: Relevance
“…This indicates that areas with diverging trends are corresponding to regions with low or negative correlations between LOS and GSI in the NH. This pattern may be due to distinct responses of vegetation phenology and productivity to the ongoing warming in high northern latitudes [54,[68][69][70]. In agreement with the result from this study, Park et al [70] found that vegetation productivity has continuously increased during 2000-2014 compared to decreasing LOS in the boreal and arctic regions of NH.…”
Section: Converging/diverging Trends and Correlations Between Los Andsupporting
confidence: 88%
“…This indicates that areas with diverging trends are corresponding to regions with low or negative correlations between LOS and GSI in the NH. This pattern may be due to distinct responses of vegetation phenology and productivity to the ongoing warming in high northern latitudes [54,[68][69][70]. In agreement with the result from this study, Park et al [70] found that vegetation productivity has continuously increased during 2000-2014 compared to decreasing LOS in the boreal and arctic regions of NH.…”
Section: Converging/diverging Trends and Correlations Between Los Andsupporting
confidence: 88%
“…So understanding the factors confluxes is essential to improve the predictability annual GPP 8 , but also correlates with net ecosystem CO 2 exchange 5 .…”
mentioning
confidence: 99%
“…As attempted by Xia et al (2015), factors related to leaf area (phenology and vegetation structure) and photosynthetic capacity (physiology) could be combined using an appropriate metric. The simulated GPP trend occurred heterogeneously over the land area.…”
Section: Mechanistic Findings From Benchmarkingmentioning
confidence: 99%